Correlation of coronary artery atherosclerosis typing and luminal narrowing with ischemic myocardial lesions in post mortem heart specimens: a four year retrospective study - Dr. Pawan Singh; Dr. Rahul N. Satarkar; Dr. Shivani Kalhan; Dr. Sonia Hasija; Dr. Bhawna; Dr. Ashok Sangwaiya; Dr. Suraj Chawla (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Atherosclerosis accounts for a large proportion of cardiovascular system associated morbidity and mortality. Coronary artery disease (CAD) is the leading cause of global deaths with about 80% of burden occurring in developing countries. Material & Methods: In order to assess the magnitude of the problem, a retrospective study of autopsy cases for the presence of atherosclerotic lesions of coronary arteries and associated ischemic cardiac lesionswas under taken from January 2013 to December 2017. Also, correlation of the atherosclerosis with ischemic heart diseases was studied. Result: Total number of heart specimens received in department of Pathology during four years were 272. Out of these 57 were autolyzed and were excluded from the study. Significant atherosclerotic lesions were seen in 54(25.11%) and 64(29.76%) cases in right and left coronary arteries respectively and were statistically significantly higher among age group > 41 years as compared to those with age <41 years, overall atherosclerotic lesions were significantly higher in age groups >41 years as compared to <41 years. Conclusion: Maximum number of significant cardiac lesion were associated with atherosclerotic type VIII lesions (75%) followed by type VII (66.66%) and type VI (33.33%). Maximum number of significant myocardial lesions were associated with grade IV (66.66%) coronary luminal narrowing followed by grade III (45.71) and grade II (38.46). The study also showed significant correlation between the higher grade of the coronary atherosclerotic lesions and the ischemic heart disease.